2013
DOI: 10.3390/rs5084088
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Synthetic Aperture Radar Surface Winds and Deep Water Velocity in the Amundsen Sea, Antarctica

Abstract: Abstract:The recent observed thinning of the glacier ice shelves in the Amundsen Sea (Antarctica) has been attributed to warm deep currents, possibly induced by along-coast winds in the vicinity of the glacial ice sheet. Here, high resolution maps of wind fields derived from Synthetic Aperture Radar (SAR) data have been studied and correlated with subsurface measurements of the deep water velocities in the Amundsen Sea area. Focus is on periods with low ice coverage in 2010 and 2011. In 2010, which had compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The hindcast showed that temperatures above the melting point over ASE ice shelves are largely insensitive to either the longitudinal location of the ASL or the polarity of the SAM, in both cases therefore having little impact on surface melting. However, both of these drivers are responsible for pronounced changes in the zonal wind stress over the ASE continental shelf edge, which influences ice shelf stability by controlling whether CDW can flow onto the continental shelf and reach the glaciers via glacial troughs (Carvajal et al, ; Dutrieux et al, ; Jenkins et al, ; Thoma et al, ). An eastward shift of the ASL causes anomalous westerly winds over the continental shelf edge near Getz Ice Shelf, while positive SAM episodes cause anomalous westerly winds over the sectors of the continental shelf edge that includes Pine Island, Thwaites, and Abbot Ice Shelves, increasing the flow of warm CDW onto these regions of the continental shelf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hindcast showed that temperatures above the melting point over ASE ice shelves are largely insensitive to either the longitudinal location of the ASL or the polarity of the SAM, in both cases therefore having little impact on surface melting. However, both of these drivers are responsible for pronounced changes in the zonal wind stress over the ASE continental shelf edge, which influences ice shelf stability by controlling whether CDW can flow onto the continental shelf and reach the glaciers via glacial troughs (Carvajal et al, ; Dutrieux et al, ; Jenkins et al, ; Thoma et al, ). An eastward shift of the ASL causes anomalous westerly winds over the continental shelf edge near Getz Ice Shelf, while positive SAM episodes cause anomalous westerly winds over the sectors of the continental shelf edge that includes Pine Island, Thwaites, and Abbot Ice Shelves, increasing the flow of warm CDW onto these regions of the continental shelf.…”
Section: Discussionmentioning
confidence: 99%
“…The recent substantial grounding‐line retreat and mass loss of ASE glaciers are/have been driven mainly by melting below the ice shelves due to intrusions of relatively warm circumpolar deep water (CDW) along glacial troughs that cross the AS continental shelf (Jenkins et al, ; Payne et al, ; Prichard et al, ). The rate of delivery of CDW onto the continental shelf is partially controlled by the direction and magnitude of zonal wind stress at the continental shelf edge, with westerly winds causing inflow of CDW onto the shelf (Carvajal et al, ; Dutrieux et al, ; Jenkins et al, ; Thoma et al, ). Relatively low‐magnitude surface melting during austral summer (December‐January‐February) has also been observed across ASE ice shelves (Tedesco, ; Trusel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Winds over the Amundsen Sea shelf break are thought to modulate transport of warm CDW onto the continental shelf, with stronger westerly winds leading to greater CDW transport (Thoma et al 2008;Carvajal et al 2013;Wåhlin et al 2013). The mean ERA-Interim winds near the coast are easterlies and the winds over the shelf break vary seasonally, but are on average weakly easterly.…”
Section: Regional Differences In the Ice Shelf Basal Meltmentioning
confidence: 98%
“…) Wåhlin et al (2013) and Assmann et al (2013) also found eastward wind at the shelf break to be important in the exchange, observing depthindependent fluctuations at weatherband frequencies along the eastern wall of the canyon that correlated with the eastward wind. Carvajal et al (2013) used the same mooring data as Wåhlin et al (2013) and found that including higher spatial resolution synthetic aperture radar winds improved the statistical correlation with the subsurface currents. They also suggested that sea ice cover may mitigate the ocean's ability to respond to events on time scales of a few days or less.…”
Section: How Do Acc Waters Influence Subglacial Cavities?mentioning
confidence: 99%